(untitled) (Information systems and technologies security, 2019)
This article presents simulation modeling process as the way to study the behavior of the Information Security system. Graphical Network Simulator is used for modeling such system and Kali Linux is used for penetration testing and security audit. To implement the project GNS3 package is selected. GNS3 is a graphical network emulator that allows you to simulate a virtual network of more than 20 different manufacturers on a local computer, connect a virtual network to a real one, add a full computer to the network, Third-party Applications for network packet analysis are supported. Depending on the hardware platform on which GNS3 will be used, it is possible to build complex projects consisting of routers Cisco, Cisco ASA, Juniper, as well as servers running network operating systems. Using modeling in the design of computing systems, you can: estimate the bandwidth of the network and its components; identify vulnerability in the structure of computing system; compare different organizations of a computing system; make a perspective development forecast for computer system; predict future requirements for network bandwidth; estimate the performance and the required number of servers in the network; compare various options for computing system upgrading; estimate the impact of software upgrades, workstations or servers power, network protocols changes on the computing system. Research computing system parameters with different characteristics of the individual components allows us to select the network and computing equipment, taking into account its performance, quality of service, reliability and cost. As the cost of a single port in active network equipment can vary depends on the manufacturer’s equipment, technology used, reliability, manageability. The modeling can minimize the cost of equipment for the computing system. The modeling becomes effective when the number of workstations is 50-100, and when it more than 300, the total savings could reach 30-40% of project cost.